Concerning the Prevalence of HPV Genotypes and the Evaluation of Pap smear Results in Iranian Population: An Update - Sina Neshat; Padideh Daneii; Negar Neshat; Sina Raeisi; Saba Raeisi; Seyed Mohammad Malakooti; Noushin Afshar Moghadam (Iranian Society of Pathology, 2021)
Human papillomavirus infection is one of the most common genital infections. More than 100 types of the virus have been identified, most of which can infect the genital mucosa. The virus is associated with cancerous and precancerous lesions of the cervix. Some types, such as human papillomavirus 16 and 18, are highly carcinogenic; some other types, such as human papillomavirus 6 and 11, are mildly carcinogenic, with HPV 31.33 in between. This study describes the relationship between different types of HPV infection and the findings of a Pap smear. In this prospective study, 1,500 samples from patients who admitted to a private Pathology Laboratory in Isfahan were collected during the years 2019-2020. Two samples were collected from each patient, one for Pap smear study and the other for polymerase chain reaction (PCR) test to detect different types of human papillomavirus (HPV) infection. In a study of 1,500 samples, 236 were positive for Papillomavirus (HPV) infection in Pap smear. By examining the genotype of positive examples, it was found that 14.8% of the samples were infected with type 16, and 1.7% were infected with type 82. HPV infection is common in Iran and is almost similar to European countries such as Germany and Spain. We also found that using a polymerase chain reaction (PCR) method to detect HPV viruses in vaginal secretions could be very useful. Our findings also show which disease is most associated with each type of HPV.